Comparison of coseismic velocity changes estimated by cross-correlation of ambient seismic noise for earthquakes in south Korea and Japan - Faisal Umer; Tae Woong Chung; Muhammad Zafar Iqbal; Saleem Iqbal (Scientific Reports)
Abstract Ambient noise cross-correlation has been widely used to observe post-earthquake temporal velocity variations. Comparative studies are essential for assessing seismic hazards and clarifying the relationship between velocity variation and magnitude. However, very few comparative studies by earthquake magnitude have been conducted, particularly for magnitudes smaller than 6. In 2016 and 2017, southeastern Korea experienced the two most damaging earthquakes of the past 250 years: the Pohang earthquake (M 5.4) and Gyeongju earthquake (M 5.8). This study compared the coseismic velocity variations of these earthquakes with those observed in the M 7.3 Kumamoto and M 6.6 Tottori earthquakes, which occurred in Japan in 2016. In this study, the moving window cross-spectral analysis revealed different curves for bidirectional cross-correlations, a difference that has not been addressed in previous studies. This discrepancy was most likely caused by data deficiencies due to prolonged aftershocks or by instability from small-magnitude earthquakes recorded by surface seismometers in Korea. The average velocity decrease between forward and reverse order pairs correlated well with earthquake magnitude, except in the case of the Korean earthquake. Our devised measure based on aftershock activity suggests that the large decrease in the Pohang earthquake was due to non-coseismic noise in addition to instability.